2018
DOI: 10.1111/idj.12383
|View full text |Cite
|
Sign up to set email alerts
|

Roles of community pharmacists in improving oral health awareness in Plateau State, Northern Nigeria

Abstract: Introduction There is poor oral health awareness in Nigeria because of limited access to correct information on oral health as well as a lack of oral health‐care providers. The purpose of this study was to describe the roles of community pharmacists (CPs) in Plateau State, Northern Nigeria, as sources of oral health information in their communities. Methods A quantitative cross‐sectional study on CPs spanning the entire State. Data collection was a survey method using a structured paper‐based self‐administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…However, this study revealed that only 8 (7%) of the community pharmacies were located in the rural areas while 86 (77%) were cited in urban centres. While this finding agrees with evidence from similar studies (Ekpenyong et al, 2018;Taiwo, Panas, 2018;, it has important implications for the quest for universal health coverage in Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…However, this study revealed that only 8 (7%) of the community pharmacies were located in the rural areas while 86 (77%) were cited in urban centres. While this finding agrees with evidence from similar studies (Ekpenyong et al, 2018;Taiwo, Panas, 2018;, it has important implications for the quest for universal health coverage in Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…It was interesting to identify the topics that pharmacists wished to learn during training programs. Hence, they have chosen either topics that are barely discussed with the patients and for which they expressed a very low level of confidence (such as gum and denture problems) aiming at learning something new, or frequent oral condition/products on which pharmacists provided advices (such as toothache and prevention of caries as well as oral care products) so they go on with fulfilling a meaningful role as oral health advisers (Taiwo and Panas, 2018). Patients asked mainly about the best toothpaste/toothbrush/mouthwash combination with reasonable price for specific oral conditions such in orthodontic/post-operative patients, or for decay prevention, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[81][82][83] Attitudes Pharmacy professionals presented general interest in further involvement in DOHC such as identifying dental and oral related issues, 72 providing oral health advice, 25,26,28,29,32,33,36,54 performing community-based assessments and preventative services, 12,33,38,72 and promotional activities. 25,26,28,31,33,34,37,38,42,72,84 Only 7.6% of surveyed UK pharmacists believed that DOHC promotion was part of their current pharmacy service contract. 34 Most pharmacy support staff believed they had a role in promoting good oral health 12 or in providing education.…”
Section: Knowledgementioning
confidence: 99%